History of Post Modernism (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The first challenge in discussing 'postmodernism' is that it is a highly imprecise term that might signify multiple things depending on the context. It makes sense to think of it as the "post-" of "modernism"—something that comes after modernism in general. These days, the term "modernism" only describes a collection of literary and artistic movements and advancements, including writers like Joyce, Proust, and Eliot, as well as movements like surrealism and cubism. There is much more to the phrase postmodernism than that. It is even more commonly attributed to a number of philosophers—Lyotard, Foucault, and Derrida are among the most well-known—whose struggle is with the Enlightenment and its main legacies, particularly Marxism, rather than with Modernism, as all of them value modernist art.